Racial and Community Wealth Disparity the Bane of HBCUs - A Wealth Ecology Model Relational Perspective (Global Journal of Management and Business Research, 2022)
Abstract not found
Keywords: racial wealth disparity; median household wealth; anchor mission; behavioral intention; school choice